(untitled) (Global Journal of Medical Research, 2023)
A retrospective data collection of patients with primary bloodstream infection diagnosis admitted to the surgical and pediatrics intensive care units of Dr Jeser Amarante Faria Children s Hospital between March 2016 and March 2020 with 28 days or more of age In this study 122 medical records were included Patients under 1 year of age represent most of the sample 72 95 and those admitted to the surgical unit were the most affected by bloodstream infection 54 10 The main comorbidity at admission was heart disease followed by pneumonia and bronchiolitis The average time to infection from device insertion was of 14 76 days Bloodcultures showed microorganism growth being the main agents found Serratia marcescens 10 66 Staphylococcus epidermidis 10 66 and Pseudomonas aeruginosa 8 20